2013
DOI: 10.1038/jcbfm.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Noise on Bold-Mediated Vessel Size Imaging Analysis Methods

Abstract: Vessel size imaging (VSI) is a magnetic resonance imaging (MRI) technique that aims to provide quantitative measurements of tissue microvasculature. An emerging variation of this technique uses the blood oxygenation level-dependent (BOLD) effect as the source of the imaging contrast. Gas challenges have the advantage over contrast injection techniques in that they are noninvasive and easily repeatable because of the fast washout of the contrast. However, initial results from BOLD-VSI studies are somewhat contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…217 The off-label use of the MR contrast agent Ferumoxytol has also been explored recently as an alternative to gadolinium-based VSI in patients with an array of diseases 218 such as acute ischemia 219 and those with advanced metastatic disease outside the brain. 220 Recently, BOLD-based VSI 189 was used to increase the microvascular specificity of fMRI. 221 There are numerous technical considerations regarding image acquisition, tracer kinetic modeling, image processing, and data interpretation that need to be borne in mind when employing DSC 206 and DCE 205 MRI protocols.…”
Section: Mag Ne Ti C Re Sonan Ce Imag Ing (Mri)mentioning
confidence: 99%
“…217 The off-label use of the MR contrast agent Ferumoxytol has also been explored recently as an alternative to gadolinium-based VSI in patients with an array of diseases 218 such as acute ischemia 219 and those with advanced metastatic disease outside the brain. 220 Recently, BOLD-based VSI 189 was used to increase the microvascular specificity of fMRI. 221 There are numerous technical considerations regarding image acquisition, tracer kinetic modeling, image processing, and data interpretation that need to be borne in mind when employing DSC 206 and DCE 205 MRI protocols.…”
Section: Mag Ne Ti C Re Sonan Ce Imag Ing (Mri)mentioning
confidence: 99%
“…The simulations above were repeated on networks populated by two different distributions of vessel radii, referred to here as the Lauwers (Lauwers et al, 2008) and Frechet (Germuska et al, 2013) distributions, and shown in Fig. 4.…”
Section: Figmentioning
confidence: 99%
“…For the vessel-size distributions, the Lauwers distribution was obtained using the parameters for the complete vessel network in (Lauwers et al, 2008) with the radii ranging from 3.0-40 µm. The Frechet distribution was implemented in MATLAB using the gevrnd function with the input parameters µ = 10.1 µm, σ = 5.8, and k = 0.41 taken from (Germuska et al, 2013) and with the radii ranging from 2.5-60 µm.…”
Section: Simulationsmentioning
confidence: 99%
“…83,94 Thus, the current clinical hardware and imaging protocols limit the traditional VSI estimate to vessel radii considered larger than ‘very small’ (>2 µm) but smaller than ‘very large’ (<50 µm). 94,101,102 The range of vessel calibres that can be acceptably defined using BOLD-VSI is probably even narrower because of the inherent small changes in magnetic susceptibility during activation of the target tissue. 94 …”
Section: Vessel-calibre Mrimentioning
confidence: 99%
“…86 BOLD-VSI analyses based on gas challenges is also influenced by vasodilation. 101 Increased cerebral vasodilation and flow is observed for hypercapnia (abnormally elevated CO 2 concentrations in the blood), whereas the opposite effect is seen in hypocapnia (low blood CO 2 levels); 112 however, the effects of gas-induced vasodilation on blood volume and, therefore, BOLD-VSI are not fully understood, 101 although venous volume fractions seem to be relatively unaffected by vasodilation. 113 …”
Section: Vessel-calibre Mrimentioning
confidence: 99%